Insulin-Like Peptide Signaling in Mosquitoes: The Road Behind and the Road Ahead - Sharma, Arvind; Nuss, Andrew B.; Gulia-Nuss, Monika (Frontiers in Endocrinology, 2019)
Insulin signaling is a conserved pathway in all metazoans. This pathway allowed primordial metazoans to respond to a greater diversity of environmental signals by modulating nutritional storage, reproduction, and longevity. Most of our knowledge of insulin signaling in insects comes from the model insect Drosophila melanogaster, where it has been extensively studied and shown to control several physiological processes. Mosquitoes are the most important vectors of human disease in the world and their control constitutes a significant area of research. Recent studies have shown the importance of insulin signaling in multiple physiological processes such as reproduction, innate immunity, lifespan, and vectorial capacity in mosquitoes. Although insulin-like peptides have been identified and functionally characterized from many mosquito species, a comprehensive review of this pathway in mosquitoes is needed. To fill this gap, our review provides up-to-date knowledge of this subfield.